2009
DOI: 10.1111/j.1439-0531.2009.01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Filament Keratin Dynamics During Oocyte Maturation Requires Maturation/M-Phase Promoting Factor and Mitogen-Activated Protein Kinase Kinase Activities in the Hamster

Abstract: Research related to intermediate filaments in mammalian oocytes remains poorly advanced. We investigated keratin reorganization in oocytes during meiotic maturation using immunofluorescence, and examined effects of inhibitors for cdc2 and mitogen-activated protein kinase kinase (MAPKK) on keratin assembly. In germinal vesicle (GV) oocytes (n = 26), large and oval-shaped aggregates of non-fibrillar keratin were found in the cortical ooplasm (designated as a 'cortical' pattern). The delicate network of keratin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Once this relocation ends, the MLBs begin to lose mass and they readily disintegrate before the follicle attains the full antral development. It has been indicated that cytokeratins (Kabashima et al, 2010), as well as their non‐fibrillar state (Gall et al, 1989), are synthesized during oocyte growth. The lack of remarkable quantities of IFs during the early growth phases of the oocyte continues in a phase with zona pellucida, in which many IFs are present in the finger‐like, cytoplasmic protrusions of the oocyte (Stage IV).…”
Section: Discussionmentioning
confidence: 99%
“…Once this relocation ends, the MLBs begin to lose mass and they readily disintegrate before the follicle attains the full antral development. It has been indicated that cytokeratins (Kabashima et al, 2010), as well as their non‐fibrillar state (Gall et al, 1989), are synthesized during oocyte growth. The lack of remarkable quantities of IFs during the early growth phases of the oocyte continues in a phase with zona pellucida, in which many IFs are present in the finger‐like, cytoplasmic protrusions of the oocyte (Stage IV).…”
Section: Discussionmentioning
confidence: 99%